The exon structure of the mouse Sc1 gene is very similar to the mouse Sparc gene. - McKinnon, P J; Kapsetaki, M; Margolskee, R F

(untitled) (Genome Research, 1996)
Sc1 and Sparc are two extracellular proteins sharing similarity in their carboxyl terminus, with 63% identity over a 232-amino-acid region. We have cloned and mapped the genomic locus of mouse Sc1. The mouse Sc1 gene contains 11 exons spanning approximately 35 kb of DNA. The genomic structure (exon/intron boundaries) of Sc1 exons 6 to exon 11 is identical to those of the similar portion of the Sparc gene. This suggests that Sc1 and Sparc originated from a common ancestral gene. Using fluorescence in situ hybridization analysis, Sc1 was localized to band 5E4 of mouse chromosome 5.